Peran Kuliah Kerja Nyata (KKN) Berbasis Masjid Pada Pengabdian di Masyarakat Desa Kembang Seri, Talang Empat, Bengkulu Tengah - Salma Azhar Fikriyah; Revi Hardiyanti; Rina Selvia Sari; Rahmi Hardianti; Zela Monika; Dela Putri Wati; Eliza Indayana; Wahyu Nurrahman; Haris Aditiya Pratama; Al-Padli; Yusnelma Eka Afri (jurnal ABDIMAS Indonesia, 2024)
Community service activities through the co-curricular program of KKN or Kuliah Kerja Nyata (Community Service), is an activity of community mentoring by students in an effort to develop the social, religious, and socio-cultural potential of the local community. At the same time, it is one form of student contribution in addressing the problems that exist in the community. This study aims to examine the role of KKN in providing education to children and increasing environmental awareness in Kembang Seri Village, Central Bengkulu Regency. The method used in this research is observation. KKN students participated in learning activities for children, environmental cleanup, legal counseling, and providing education to children about the importance of religious and social knowledge. The results of the study show that through KKN, educational and environmental awareness in Kembang Seri Village has increased significantly. The community has begun to understand the importance of maintaining religious and social teachings or knowledge, as well as cleanliness and caring for their surroundings. Children also showed an increase in religious and social knowledge through educational activities conducted by KKN students.